Social Theology of the Free Nutritious Meal Program: Reinterpretation of QS. Al-Baqarah: 168 in Tafsir Al-Azhar - Baeti Rohman (ZAD Al-Mufassirin, 2026)
This study aims to provide a theological reinterpretation of Quranic verse (QS.) Al-Baqarah: 168, shifting its focus from a mere jurisprudential (fiqh) guide for personal consumption toward a foundational framework for political ethics and public policy (siyasah syar'iyyah). The primary objective is to redefine the term thayyiban within the context of the national nutritional emergency (stunting) and the strategic efforts to enhance the nation's cognitive intelligence in pursuit of the "Golden Indonesia 2045" vision. Utilizing a descriptive-analytical qualitative method with an interdisciplinary approach—integrating textual studies (Tafsir Al-Azhar), public nutrition science, and economic sociology—this research analyzes the Nutritious Free Meal (Makan Bergizi Gratis / MBG) Program as a theological mandate for the preservation of life (hifz al-nafs) and the preservation of intellect (hifz al-‘aql). The findings indicate that the thayyiban criteria in the Quran scientifically correlate with the fulfillment of essential animal protein intake, which is critical for brain synapse development. Sociologically, the MBG program serves as an instrument of Islamic social justice aimed at breaking the cycle of structural poverty. Buya Hamka’s interpretation further legitimizes the premise that state authorities are obligated to guarantee the quality of the populace's nutrition. Ultimately, national nutritional failure is not merely a health crisis but a form of neglect toward human dignity within the framework of transformative social theology.